Non-university higher Education in Europe - Taylor, James S. [Herausgeber]; Brites Ferreira, José [Herausgeber]; de Lourdes Machado, Maria [Herausgeber] (Springer Netherlands, 2008)
"Higher education throughout the world is facing rapid change. Despite the enormous attention devoted to that reality, this volume fills an important void. It describes and offers critical comparisons between the systems in 10 European countries. The book brings together the thinking of leading scholars on the non-university sectors in Austria, Belgium, Finland, Germany, Ireland, the Netherlands, Norway, Portugal, Spain, and the United Kingdom, with a chapter devoted to each country. National case studies are presented for the non-university sector in these countries that address issues such as historical developments, policy changes, governance structures, levels of institutional autonomy and future trends. The editors offer a critical comparative analysis of the systems in these countries followed by a probing look into the future of the non-university sector in Europe. The book is essential reading for those who want a comprehensive, timely and in-depth understanding of the European non-university sector. It will be informative to anyone involved in system or institutional governance, as well as those pursuing research." (Publisher, BIBB-Doku)

Table of contents: Preface / James S. Taylor et al ; Introduction: The End of Alternatives to Universities or New Opportunities? / Ulrich Teichler ; The Role of the Non-University Sector in Austrian Higher Education / Elsa Hackl ; Questioning the Binary Divide: Non-University Higher Education in Flanders (Belgium) / Jef C. Verhoeven ; Polytechnics in Finnish Higher Education / Jussi Välimaa and Marja-Liisa Neuvonen-Rauhala ; German Fachhochschulen: Towards the End of a Success Story? / Matthias Klumpp and Ulrich Teichler ; The Non-University Sector in Irish Higher Education / Patrick Clancy ; Shifting Boundaries in Higher Education: Dutch Hogescholen on the Move / Jeroen Huisman ; The Non-University Higher Education Sector in Norway / Svein Kyvik ; The Polytechnic Higher Education Sector in Portugal / José Brites Ferreira et al ; The Non-University Sector in the Spanish System of Higher Education / Josep M. Bricall and Martí Parellada ; Higher Education outside the Universities: The UK Case / John Brennan and Ruth Williams ; Reframing the Non-university Sector in Europe: Convergence or Diversity? / M. Lourdes Machado et al
Keywords: S 1.4 Hochschulbildung; I 2.1 Deutschland; I 2.2.1 Westeuropa; Hochschulbildung; Höhere Berufsbildung; Fallstudie; Internationaler Vergleich; Bundesrepublik Deutschland; Belgien; Finnland; Irland; Niederlande; Norwegen; Österreich; Spanien; Portugal; Vereinigtes Königreich